On the effect of parent–aneurysm angle on flow patterns in basilar tip aneurysms: Towards a surrogate geometric marker of intra-aneurismal hemodynamics - Ford, Matthew D.; Lee, Sang-Wook; Lownie, Stephen P.; Holdsworth, David W.; Steinman, David A. (Journal of biomechanics, 2008)
As a part of previous computational fluid dynamic (CFD) validation studies, particle image velocimetry (PIV) of two anatomically realistic basilar artery tip aneurysm models revealed two distinct types of flow (one of which has yet to be reported in the literature), characterized by the location and strength of the intra-aneurismal vortex. We hypothesized that these distinct “hemodynamic phenotypes” could be anticipated by a simple geometric parameter: the angle of the aneurysm bulb relative to the parent artery. An idealized basilar tip aneurysm model was constructed to allow independent control of this angle, and CFD simulations were carried out for angles ranging from 2° to 30°, these extremes corresponding to the angles measured from the two anatomically realistic models. The gross hemodynamics predicted by the idealized model for 2° and 30° were consistent with those seen in the corresponding anatomically realistic models. For the idealized model, the flow type switched at an angle between 8° and 12°. Sensitivity studies suggested that, near these angles, the hemodynamic phenotype was sensitive to inflow momentum. Outside this range, however, the parent–bulb angle appeared to be a robust predictor of hemodynamic phenotype. Our findings suggest that blood flow dynamics in basilar artery tip aneurysms fall into one of the two broad phenotypes, each subject to distinct hemodynamic forces. That the general features of these flow types may be anticipated by a relatively simple-to-measure geometric parameter could help ease the introduction of hemodynamic information into routine clinical decision-making.